A Sulfur‐Rich Copolymer@CNT Hybrid Cathode with Dual‐Confinement of Polysulfides for High‐Performance Lithium–Sulfur Batteries. Issue 11 (30th December 2016) - Hu, Guangjian; Sun, Zhenhua; Shi, Chao; Fang, Ruopian; Chen, Jing; Hou, Pengxiang; Liu, Chang; Cheng, Hui‐Ming; Li, Feng
Abstract : A sulfur‐rich copolymer@carbon nanotubes hybrid cathode is introduced for lithium–sulfur batteries produced by combining the physical and chemical confinement of polysulfides. The binderfree and metal‐current‐collector‐free cathode of dual confinement enables an efficient pathway for the fabrication of high‐performance sulfur copolymer carbon matrix electrodes for lithium–sulfur batteries.